2019
DOI: 10.1155/2019/3979741
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior and Its Influencing Factors on Engineered Cementitious Composite Linings

Abstract: A 1/5-scale model test was used to analyze and compare the mechanical responses of engineered cementitious composite (ECC) lining and traditional concrete lining under vertically concentrated loading. Test results indicate that the major failure mode of the lining cross section is controlled by tensile stress. ECC linings express better cracking control capability and deformation performance than the traditional concrete tunnel linings. On this basis, the effects of loading direction, material tensile properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…For simplicity, the present tests used vertical centralised loading to investigate the mechanical properties of the reinforced structure under loosening vertical soil pressure, which is similar to the loading method of existing experimental studies [22,23]. Taking the common two-lane road tunnel C30 reinforced concrete lining as the research object [24], based on the similarity theory, for the centralised loading method, the model lining specimens can be made of prototype materials when the effect of structural deadweight is not considered [25]. Therefore, this paper produced a test model according to the material similarity ratio of 1:1 and the geometric similarity ratio of 1:5.…”
Section: Experimental Content and Similar Designmentioning
confidence: 99%
See 1 more Smart Citation
“…For simplicity, the present tests used vertical centralised loading to investigate the mechanical properties of the reinforced structure under loosening vertical soil pressure, which is similar to the loading method of existing experimental studies [22,23]. Taking the common two-lane road tunnel C30 reinforced concrete lining as the research object [24], based on the similarity theory, for the centralised loading method, the model lining specimens can be made of prototype materials when the effect of structural deadweight is not considered [25]. Therefore, this paper produced a test model according to the material similarity ratio of 1:1 and the geometric similarity ratio of 1:5.…”
Section: Experimental Content and Similar Designmentioning
confidence: 99%
“…As can be observed, the reinforced structure encountered four critical places under the vertical load: the reinforcement point (A), the point of spalling at the interface between the steel plate and UHPC (B), the point of peak load (C), and the failure point (D). The damage load was 85% of the peak load [24]. The process of vault subsidence is divided into four stages: (1) Before reinforcement, under the loading of vertical load at the top, the load increased nearly linearly with the increase in displacement.…”
Section: Relationship Between Load and Displacementmentioning
confidence: 99%
“…The energy dissipation factor is the ratio of the energy consumed by a hysteresis loop to load and unload for a circle to the total energy of loading and unloading. The energy dissipation factor E ′ of the specimen [15][16][17][18] can be calculated by formula (5).…”
Section: Structural Systemmentioning
confidence: 99%
“…Uniaxial compression test of the rubber plate indicated that the compressive stiffness of the rubber plate was 3.38 MN/m. A total of eight rubber plates were used to simulate the formation constraints of the lining model test and the equivalent formation resistance coefficient was calculated to be 27.9 MPa/m [22][23][24]. To investigate the effect of voids on mechanical properties of tunnel linings, five model test conditions were set up as follows.…”
Section: Model Test Schemementioning
confidence: 99%